Fifty years of American polarization and the changing roles of faith communities. Issue 1 (6th March 2018) - LaHurd, Carol Schersten
Abstract: The 2016 election of Donald Trump as president and the first year of his administration have been accompanied by intensified social and political divides in the United States. A comparison of today's polarization with that during the Vietnam War and civil rights movement of the 1960s suggests strategies for bridging the divides—and in particular for an expanding role by faith communities.